Perancangan Dashboard SPC Excel Sebagai Alat Analisis Kinerja Mesin Filling Pada PT SMART Tbk. - Ancelloti Alessandro; Nova Sepadyati (Jurnal Titra, 2019)
PT SMART, Tbk, is an agribusiness company that produce product from processed palm oil, the most well known product is cooking oil. Cooking oil product has quality specification to fulfill customer’s satisfaction, one of them is conformity of actual volume with volume that printed on the label. This quality specification affected by filling machine performance, therefore tool that can help create machine performance evaluation is needed. The purpose of this study is to design a dashboard  that can reduce time to process data into statistic parameters and to test the properness number of samples in current condition. Design of the dashboard will use Microsoft Excel program with Visual Basic for Application (VBA). The performance evaluation  is using statistic parameters (Cp, Cpk, and Sigma), while the properness of sample number is using two sample T-test. Dashboard reduce the processing time from 230% up to 763% and majority of the machine performance are lower than the standard. The result of number of samples’ test showed that total samples of 98 per hour has different significantly against total samples of 5 per hour, so that the sample number must be increased in order to represent the actual condition.